TRIBOLOGICAL PROPERTIES OF MINERAL BASE OILS WITH TUNGSTEN DISULPHIDE (WS2) NANOPARTICLES IN BOUNDARY LUBRICATION CONDITIONS - Setyo Widodo; M Hanifuddin; Rona Malam Karina (Testing Center for Oil and Gas LEMIGAS, 2016)
Friction affects the efficiency of a mechanical system. This paper discusses the influence of Tungsten Disulphide (WS2) as a friction modifier (FM). Friction and wear characteristics of base oil as a result of the addition of 0.1% and 0.5 % weight of WS2 were studied. WS2 nanoparticles were mixed with base oil using magnetic stirrer at 50oC for 60 minutes, then were homogenized in an ultrasonic homogenizer for 1 hour. Friction and wear characteristic of these mixtures were tested using four-ball and HFRR test-rig. The results show that the addition of both 0.1% and 0.5% WS2 nanoparticles increased by around 40% the anti-wear characteristic of mineral base oil group I and 12% for other groups of base oils. The increase in friction coefficients was in a range of 7.5% to 35% as a result of the addition of additives.